The Role of Weverse Social Media In Building BTS Boygroup Fans' Loyalty - Dwi Amanda Simanjuntak; Muhammad Irwan Padli Nasution; Rahmi Syahriza (LP2M IAIN Palopo, 2025)
This study aims to analyze the role of Weverse's social media in building fan loyalty to the BTS boy group. Weverse is a digital community platform that allows direct interaction between artists and fans through various features such as comments, chat, live streaming, as well as access to exclusive content and official merchandise purchases. This research uses a qualitative approach with phenomenological methods. Data was collected through indirect interviews in the form of an open-ended questionnaire disseminated through Google Forms, which was designed to allow respondents to deliver narrative answers based on their personal experiences. The research subjects consisted of five members of the ARMY fandom who were active in using the Weverse platform. The results show that the real-time interaction and live streaming features in Weverse are able to form parasocial relationships that strengthen fans' emotional attachment. In addition, access to exclusive content and ease of transactions on the Weverse Shop also encourage loyal behaviors such as repurchases, cross-purchases, and recommendations to other users. This loyalty is reflected in the consistency of fans in following BTS's activities on Weverse even though other alternative platforms are available. This research confirms that Weverse not only serves as a communication medium, but also as an effective strategy in strengthening fan loyalty and consumption behavior through immersive emotional experiences.